Towards the development of intelligent control and monitoring schemes for smart metering systems - Ajeigbe, Olusayo Adekunle; Jordaan, Jacobus Andries (Edelweiss Applied Science and Technology, 2025)
The increasing demand for grid stability and energy efficiency has propelled the advancement of intelligent control and monitoring technology for smart metering systems. This study examines scholarly publications, research papers, technical reports, and industry publications over a fifteen-year period (2010–2025). The evaluation emphasizes significant technological advancements, such as blockchain-enabled energy transactions, improved bidirectional communication protocols, automated demand response systems, and the integration of IoT with artificial intelligence. Despite these advancements, ongoing challenges encompass insufficient load separation, absence of intelligent load management, difficulties in energy supply-demand equilibrium, restricted bidirectional communication, and deficiencies in device classification. The results indicate the need to include edge computing, predictive load management driven by artificial intelligence, interoperability with hybrid energy systems, and improved cybersecurity. These gaps can be addressed through multidisciplinary cooperation among engineers, data scientists, legislators, and energy companies. Future smart meters should, according to the study, utilize cutting-edge technologies to offer sustainable grid management, enhance consumer satisfaction, and advance the energy economy. By incorporating sophisticated communication protocols, load management optimization, and intelligent control mechanisms, smart metering systems may significantly improve sustainable energy solutions and modernize smart grids.